Root resorption of maxillary incisors caused by bilaterally impacted canines: An evaluation by cone-beam computed tomography - de Campos Neves, Ana Thereza Sabóia; Volpato, Luiz Evaristo Ricci; Oliveira, Thais Marchini [UNESP]; Palma, Vinicius Canavarros; Tonetto, Mateus Rodrigues [UNESP]; Bandeca, Matheus Coelho; Borges, Álvaro Henrique (Jaypee Brothers Medical Publishing, 2014)
When root resorption of incisors occurs due to impaction of maxillary canines, several factors interfere in the treatment plan, such as the location and severity of root resorption, canine position, lack of space and dental development stage. The case of severe root resorption of permanent maxillary incisors caused by bilaterally impacted permanent maxillary canines and its multidisciplinary therapeutic approach in a 12-year-old girl is presented. After clinical and imaging examination, a treatment plan was outlined including preservation of primary canines, extraction of the permanent maxillary right canine and permanent maxillary left lateral incisor followed by its replacement with the orthodontically tractioned permanent canine and esthetic restoration of the permanent maxillary anterior teeth. One year after treatment, the result was satisfactory and the remaining teeth were still asymptomatic. The risk of root resorption in children with impacted permanent maxillary canines should not be neglected thus reducing subsequent complications.
Keywords: Impacted tooth; Mixed dentition; Root resorption